Price efficiency of Islamic and conventional banks: evidence from panel data - Saw, Andrew Tek Wei; Kamarudin, Fakarudin; Abdul Latiff, Ahmad Shaharudin (Universiti Putra Malaysia, 2020)
Literature on the price efficiency of Islamic and conventional banks have focused mostly on cost efficiency while attention on profit and revenue efficiency has been lukewarm. This study examines how Islamic and conventional banks differ in terms of cost, profit and revenue efficiency. Using a sample of 18 countries with 70 Islamic and 374 conventional banks spanning from year 2009 to 2017 across the Middle East, South Asia and Southeast Asia regions, the empirical results derived from using the least squares dummy variable indicate that there is no significant difference between both types of banks. Further robustness checks utilizing random effects model also reveal similar findings. Among the sample countries, Islamic and conventional banks from Singapore, Malaysia and Qatar were found to be relatively higher in average profit efficiency compared to banks from other sampled countries, while Islamic and conventional banks from Indonesia, Iraq and Jordan were found to be relatively inefficient in generating profit. This study also found that banks from some countries did relatively better in terms of revenue efficiency compared to cost efficiency and vice versa. This indicates there is a need to look not just into the topic of costs but also how well banks fare in generating revenue.